PENGARUH LATIHAN ONE - ON - ONE SADHOW TAG TERHADAP WAKTU REAKSI PADA SISWA EKSTRAKURIKULER BOLA BASKET SMA BUDHI LUHUR RUMBAI PEKANBARU - Jais, Muhammad; Juita, Ardiah; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT : Based the results of observations conducted by researchers in the field at extracurricular activities, the researchers found that the problem is still the lack of reaction time limb muscle on extracurricular basket ball. Based on the existing problems, the researchers aim to provide a form of exercise that can increase reaction time and administration Exercise intensive program. In this study the authors only focus on one form of exercise that exercises one-on-one sadhow tag for this exercise has never been applied to students' extracurricular SMA Budhi luhur rumbai pekanbaru.This study used an experimental method, in order to determine the effect of exercise. Thus the experimental research method can be interpreted as the research methods used to find a specific treatment effect against the other in uncontrolled conditions. The first step taken is to Pree-test is a test to measure the whole body reaction before trained its reaction time. Subsequently the samples were treated namely practice one-on-one sadhow tag. Then do the final test is the post-test with thet whole body reactio, to see if there is increased after a given treatment.Data were analyzed descriptively, then further testing research hypotheses have been proposed to fit the problem is: there is influence of plyometrics exercises one-on-one sadhow tag significantly to the results of reaction time. Based on t test analysis produces Tcount of 4.8 and Ttable of 1.80. Means that Tcount> Ttable. It can be concluded that H0 rejected Ha accepted. So it can be summed up as follows: there is the effect of exercise one-on-one sadhow tag against the reaction time in the student extracurricular basket ball SMA Budhi Luhur Rumbai Pekanbaru.Keyword : Exercise One-on-one sadhow tag